Biodeterioration of stored seeds of certain arid zone tree species - D.K. PUROHIT, N.K. BOHRA and (Indian Phytopathology, 2002)
The mycoflora of stored seeds of Prosopis cineraria (Khejri) and Acacia senegal (Kumat) collected from different localities of Rajasthan, India, were studied using the blotter paper technique, and the aflatoxin producing potential of Aspergillus flavus isolates was determined. A. flavus was dominant in almost all samples tested in the blotter paper study. A. niger, A. fumigatus and A. ochraceus were also present in abundance, while species of Fusarium, Curvularia, Chaetomium, Alternaria, Stachybotrys and Rhizopus were also recorded in some of the samples. The results showed that out of 78 isolates of A. flavus from Acacia senegal, 38 isolates were toxic and produced aflatoxin in liquid medium. Aflatoxin B1 was produced by 30 isolates; 6 isolates produced aflatoxin B1 and B2 together; and 2 isolates produced aflatoxin B1, B2, G1 and G2. For Prosopis cineraria, 23 out of 54 isolates of A. flavus produced aflatoxins. B1 was produced by 21 isolates while B1 and B2 were formed by only 2 isolates. Noneof the isolates produced all four aflatoxins. A study of the biodeterioration of seeds of P. cineraria and A. senegal by A. flavus showed a reduction in reducing sugar, total soluble sugar and protein content, and an increase in phenol concentration, of the seeds.